Plastic Credits and the Extended Producer Responsibility (EPR) An Analysis of Opportunities and Challenges of PC for the EPR Implementation in Lusaka, Zambia - Skowranek, Inga (Young Academics: Nachhaltigkeitswissenschaft, 2023)
Plastic credits (PCs) could be part of the solution to the global waste problem. In this book, the author investigates whether and how plastic credits can act as a bridge on the road to implementing extended producer responsibility (EPR). While PCs can be used in the short term, EPR schemes are long-lasting processes. As both mechanisms follow similar principles, it is possible that PCs can be used in the short term to optimise the handling of plastic waste and the involvement of producers and to lay the foundations for the final goal of EPR implementation. This question is addressed through a literature review and a field study of waste management in Lusaka, Zambia.